(untitled) (Fiep Bulletin - online, 2019)
The representation of the body that is problematized in the school is anchored in the biological perspective, notconsidering the historical, social and cultural constructions of the subjects. The search for strategies of recognition of the otherand respect for diversity exists in the classes of Physical Education school, must be a constant, given the diversity ofcharacteristics and interests of the student. Thus, cultural differences should be contemplated and reach the vast majority ofstudents. This article, of a bibliographical nature, seeks to discuss aspects related to gender and corporeality in School PhysicalEducation. In addition to contributing to the understanding of many of the challenges faced by teachers, we seek to socializestrategies for future teachers in their professional work. A curriculum that works with difference represents, therefore, a politicalposition in the relations of power present in the schools.